How does credit affect yields? Lessons from potato and rice farmers in Uganda - Van Campenhout, Bjorn (International Food Policy Research Institute, 2016)
Despite favorable agro-ecological conditions, agricultural productivity in Uganda remains low. Crop intensification methods, such as the application of inorganic fertilizers and pesticides and the use of improved planting material, are promoted for in-creasing yields. But farmers are often financially constrained, leading to under-adoption of such methods. Therefore, facilitating credit provision to smallholder farmers may be an effective way to increase crop intensification and boost agricultural yields. We find that among potato and rice farmers part of the credit received indeed seems to affect productivity through in-tensification. However, a large share of credit is used for other purposes, such as paying school fees or investing in businesses or social functions. We argue that this fungibility is not necessarily problematic, as we find important indirect effects, where credit affects yields through improved agricultural knowledge transfer, market access, and social network learning effects. Our findings call for a more comprehensive approach to credit provision and a longer run perspective.